The advantages of creating a positive radiation safety culture in the higher education and research sectors*A report from the Working Group on Culture in Research and Teaching. (30th November 2015) - Coldwell, T; Cole, P; Edwards, C; Makepeace, J; Murdock, C; Odams, H; Whitcher, R; Willis, S; Yates, L
Abstract: The safety culture of any organisation plays a critical role in setting the tone for both effective delivery of service and high standards of performance. By embedding safety at a cultural level, organisations are able to influence the attitudes and behaviours of stakeholders. To achieve this requires the ongoing commitment of heads of organisations and also individuals to prioritise safety no less than other competing goals (e.g. in universities, recruitment and retention are key) to ensure the protection of both people and the environment. The concept of culture is the same whatever the sector, e.g. medical, nuclear, industry, education, and research, but the higher education and research sectors within the UK are a unique challenge in developing a strong safety culture. This report provides an overview of the challenges presented by the sector, the current status of radiation protection culture, case studies to demonstrate good and bad practice in the sector and the practical methods to influence change.